EZH2-mediated epigenetic silencing of TIMP2 promotes ovarian cancer migration and invasion - Xiaoqing Yi (Nature Portfolio, 2017)
Abstract Enhancer of zeste homolog 2 (EZH2) is often increased in malignant tumors and is involved in metastasis. EZH2 silences gene expression by tri-methylating the lysine 27 residue of histone H3 (H3K27me3). However, the mechanism underlying EZH2 promotion of ovarian cancer metastasis remains elusive. Here, we showed that EZH2 is up-regulated in ovarian cancer and is associated with tumor metastasis and poor survival by mRNA sequencing and microarray results from databases. Tissue microarray and immunohistochemistry results revealed that EZH2 was negatively correlated with the expression of tissue inhibitor of metalloproteinases 2 (TIMP2). EZH2 overexpression inhibited TIMP2 expression and promoted proteolytic activities of matrix metalloproteinases 2 and 9 and vice versa. EZH2 promoted ovarian cancer invasion and migration, which could be largely reversed by TIMP2 down-regulation in vitro and in vivo. Both H3K27me3 inhibition and demethylation could reduce methylation of the TIMP2 promoter and finally reactivate TIMP2 transcription. The presence of EZH2 and H3K27me3 at the TIMP2 promoter was confirmed by chromatin immunoprecipitation. H3K27me3 and DNA methyltransferases at the promoter were significantly increased by EZH2 overexpression. These results suggest that EZH2 inhibits TIMP2 expression via H3K27me3 and DNA methylation, which relieve the repression of MMP and facilitate ovarian cancer invasion and migration.